Relative expression of CsZCD gene and apocarotenoid biosynthesis during stigma development in Crocus sativus L. - Mir, J. I. (Springer India, 2012)
Crocus sativus is a triploid sterile plant characterized by its red stigmas, which produce significant quantities of carotenoid derivatives formed from the oxidative cleavage of β-carotene and zeaxanthin. The accumulation of three major carotenoid derivatives- crocin, picrocrocin, and safranal- is responsible for the color, bitter taste, and aroma of saffron, which is obtained from the dried stigma of Crocus. Maximum apocarotenoid accumulation occurs during fully developed scarlet stage of stigma development. Zeaxanthin is the precursor for biosynthesis of apocarotenoids. Crocus zeaxanthin 7, 8 (7, 8)-cleavage dioxygenase gene (CsZCD) encodes a chromoplast enzyme that initiates the biogenesis of these apocarotenoids by cleaving zeaxanthin. The Reverse Transcription-PCR analysis revealed that CsZCD gene expression followed different patterns during stigma development. Highest levels of CsZCD gene expression was observed in fully developed scarlet stage of stigma. Real Time PCR analysis showed that there is a sharp increase in gene expression from yellow to orange and orange to scarlet stages of stigma development. Increase in CsZCD gene expression parallels with the apocarotenoid content during the development of stigma, suggesting its regulatory role for apocarotenoid biosynthesis and stigma development in saffron. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12298-012-0131-9) contains supplementary material, which is available to authorized users.